The Impact of War on David Malouf's Novels: A Historical-Biographical Approach - Abbas, Hussein Ali (2003)
The purpose of this study is to show that Malouf's novels embody a historical fact that the author and his country Australia were severely affected by war The historical-biographical approach is applied to examine three novels by the Australian writer David Malouf Johnno, Fly Away Peter and The Great World. It is observed that in these novels war in terms of effects forms the central theme. However, the histrographical approach assumes that literary work is reflective of two histories that of the author himself and of his country Malouf's biography reveals that he is a son of a family fated by war and his childhood was shattered by events of the Second World War. The history of Australia documents that people of this country were exposed to many deadly effects of the two global wars. Therefore, Malouf's writings came to relate how war affected him and his country. In Johnno (1976), the memories of the author on his family and society under the Second World War combine to form the substance of his first fictional work. In terms of his personal life, the progress of war was a source of worry and fear for his family, and he was filled with horror when the Japanese invasion of his hometown became imminent. In terms of his country, the war took men away into Europe, and their women and children were left to meet not only the economic demands of war but also to meet the sexual needs and criminal tendency of thousands of American soldiers who supposedly had come to defend Australia against an expected Japanese invasion. The people of Australia were also thrown into an intellectual disorder as they looked for an identity that does not oblige them to go to battlefield again whenever the British are involved in a new war. In Fly Away Peter (1983), the author relates that his countrymen were vulnerable to another effect of war: death and injuries. Men, misguided by the propaganda that war makes history, came to the front lines as volunteers. They had to live the horrors of war and lose their comrades to death and injuries before they understood that war is the real enemy of human beings. The Great World (1991) shocks readers when it provides evidence of the effect of war on Australian prisoners of war in the Japanese detention camps. The effect was most destructive. This effect takes the form of food shortage, disease, mistreatment and compulsory exhausting work. These factors caused death to thousands of Australian prisoners. With these facts, the novels serve not only to document the effects of war on Malouf and his country, but also serve to provoke people into a belief that war is terrible and all should stand against any war.